Getting the Most Out of Public-Sector Decentralisation in Korea - Jones, Randall S.. (OECD Economics Department Working Papers, 2005)
This paper discusses policies to improve fiscal relations between levels of government to better meet the needs of citizens, an objective of the government's "Roadmap for Decentralisation". Although local government accounts for around half of total government spending, they have little autonomy and fiscal resources vary sharply between regions. The priority should be to enhance the independence of local authorities by establishing a clear division of responsibilities and transferring additional assignments to the local level. The general local governments should also have more influnence on education, while providing more support, through stronger linkages with the local education authorities, with a final aim of merger. The allocation of intergovernmental grants should be more transparent and the regulations attached to them should be relaxed to expand flexibility, while increasing reliance on block grants. Improving the fiscal federalism framework also requires more revenue raising power for local governments while simplifying the structure of local taxes. Greater accountability and rules are needed to ensure sound fiscal management by local governments. This Working Paper relates to the 2005 OECD Economic Survey of Korea (www.oecd.org/eco/surveys/korea)